Granular Cell Ameloblastoma: A Rare Case Report and Literature Review - Samiha Jameel Ahmed Khan; Madhuri Gawande; Alka Hande; Swati Patil; Archana Sonone (Journal of Clinical and Diagnostic Research, 2023)
Ameloblastomas are rare, benign, aggressive neoplasms of odontogenic epithelial origin. Among the various types of ameloblastomas, granular cell ameloblastoma is rare and accounts for less than 5% of the total. Granular cells are epithelial in origin. The distinct histopathological characteristics of granular cells are associated with high lysosomal content in tumour cells cytoplasm. A 43-year-old female patient presented with a painful swelling on the left-side of the jaw. The diagnosis was based on clinical, radiological and histopathological examination. A complete surgical resection was done. Histopathology showed features of granular cell ameloblastoma. The operative procedure was uneventful. Granular cell ameloblastoma has a high tendency for recurrence. Around 33.3% recurrence is reported, according to various studies. This rate is much higher than other subtypes of ameloblastoma, which are more common. Hence, it is essential to provide appropriate surgical treatment on time to prevent tumour recurrence and metastasis.This case report aims to highlight the unique features of granular cell ameloblastoma, distinguishing it from other subtypes and discussing the pathogenesis and treatment modalities.